Asuhan Keperawatan Pada Ny. A Dengan Post Sectio Caesaria Atas Indikasi Cephalopelvic Disproportion (CPD) Di Ruang Mawar RSUD Surakarta - Munawaroh, Munawaroh; , Faizah Betty R., A., S.Kep ., M.Kes (2015)
NURSINGCARE OF CLENT WITH SECTIO CAESAREA POST THEINDICATION CEPHALOPELVIC DISPROPORTION(CPD) AT RSUD SURAKARTA (Munawaroh, 2015, 68 page) ABSTRACT Background: Cephalopeivic disproportion (CPD) is caused by factors from the mother if Darri factors such as maternal pelvic abnormalities and factors of the fetus just as the fetus is too large so it is not possible to conduct normal deliveries Objective: To determine the nursing care in patients with post sectiocaesarea with cephalopelvicdisproportio (CPD) includes assessment, diagnosis, intervention, implementation, and evaluation of nursing.Results: After nursing actions during 3x24 hours pain patients showed reduced from scale 7 to 2, the milk can be met, and does not happen any signs of infection. Conclusion: Cooperation between the health care team and patient / family is indispensable for the success of nursing care for patients, therapeutic communication can encourage more cooperative patients, progressive relaxation techniques can reduce pain and is a preferred measure patient. Keywords: Post sectiocaesarea, cephalopelvic disproportion (CPD), pain, physical mobility barriers, lack of knowledge, the risk of infection.